Supplementary Material S1 from Sex-specific variation in the use of vertical habitat by a resident Antarctic top predator - Theoni Photopoulou; Karine Heerah; Jennifer Pohle; Lars Boehme (2020)
Descriptive statistics, individual maps, and data collection rules